Ovarian tumour: CT characteristics with HPE correlation - Hassan, Radhiana; Abd. Aziz, Azian; Md Ralib @ Md Raghib, Ahmad Razali; Abdullah, Suhaiza; Ab Rahman, Jamalludin (2012)
Ovarian tumour is a common neoplasm involving the female genital tract. Clinical spectrum of ovarian tumours ranges from a largely benign tumours to life-threatening, widely metastatic cancers. Ovarian cancer was the fourth commonest cancer among women in Malaysia with an age-standardized rate of 6.4 per 100,000 women. It remains a leading cause of death from gynecological malignancies. Radiologist’s ability to differentiate a benign lesion that may require conservative rather than surgical management from a malignant lesion is important for proper planning of management.